P1625HIGHER DIETARY ACID LOAD IS ASSOCIATED WITH INCREASED RISK FOR KIDNEY FUNCTION DECLINE AND GRAFT FAILURE IN KIDNEY TRANSPLANT RECIPIENTS. (6th June 2020) - Yeung, Stanley Ming Hol; Gomes-Neto, António W; C.J. Osté, Maryse; Van den Berg, Else; Kootstra-Ros, Jenny E; Sanders, Jan-Stephan; Berger, Stefan P; Carrero, Juan Jesus; De Borst, Martin; Navis, Gerjan; Bakker, Stephan
Abstract: Background and Aims: Dietary acid load is associated with low grade metabolic acidosis and might accelerate kidney function decline in patients with chronic kidney disease (CKD). We investigated whether dietary acid load, estimated as net endogenous acid production (NEAP), is associated with kidney function decline in kidney transplant recipients (KTR) and to what extent this association is mediated by variation in venous bicarbonate (HCO3 - ). Method: We used data from 642 KTR with a functioning graft ≥1 year after transplantation who were enrolled in the Transplantlines Food & Nutrition Cohort Study between 2008-2011. We applied the Frassetto equation (NEAP = (54.5 X protein (g/d) / potassium (mEq/d) - 10.2)) to calculate NEAPFFQ using intake reported in food frequency questionnaires and NEAPUrine from assessments of 24 hours urinary urea and potassium excretion. Patients were divided into tertiles of NEAP and differences across tertiles were analyzed by ANOVA, Kruskall-Wallis and Chi-Square tests, as appropriate. Cox regression models were used to study the associations between NEAPFFQ and NEAPUrine (both continuous variables and categories) with the composite endpoint kidney function decline, defined as doubling of serum creatinine or graft failure. Mediation analyses were performed to evaluate whether these associations were explained by venous bicarbonate. Results: Mean age was 53±13 years, 56.1% were men, and mean eGFR was 52±20 ml/min/1.73m 2 . Patients within the highest tertile of NEAPFFQ were younger ( P =0.04), more recently transplanted ( P =0.002), consumed less fruit and vegetables ( P <0.001), more fish ( P =0.001), less alcohol ( P =0.01), more meat ( P <0.001) and had lower serum HCO3 - concentration ( P =0.02). During a median follow-up time of 5.3 (4.1-6.0) years, 121 (18.8%) patients developed kidney function decline. In multivariable Cox regression analysis, higher NEAPFFQ (per SD increase) was associated with increased risk of kidney function decline, independent of potential confounders, including age, sex, BMI, time after transplantation, primary kidney disease, eGFR and proteinuria (adjusted HR 1.30; 95%CI 1.10-1.53, P =0.002). Compared to patients in the lowest NEAPFFQ tertile, those in the highest tertile had a >1.5 higher risk of kidney function decline (adjusted HR 1.67; 95%CI 1.07-2.62, P =0.03). We observed similar results using NEAPUrine as the study exposure (adjusted HR 1.46 per SD increase; 95%CI 1.24-1.73, P <0.001; adjusted HR 1.99; 95%CI 1.24-3.18, P =0.004 for patients in the highest versus lowest tertile of NEAPUrine ). These associations between NEAPFFQ (Figure A) and NEAPUrine (Figure B) with kidney function decline were visualized by fitting multivariable Cox regression models based on restricted cubic splines. Mediation analyses estimated that venous HCO3 - at baseline mediated 19.3% ( P =0.008) of the association between NEAPFFQ and kidney function decline and 26.5% ( P =0.002) of the association between NEAPUrine with kidney function decline. Conclusion: Higher NEAP is associated with a higher risk for kidney function decline in KTR, and this association was in part mediated by venous HCO3 - . We speculate that reducing dietary acid load might mitigate the risk of kidney function decline in KTR.